2014
DOI: 10.1097/sla.0b013e3182a6f529
|View full text |Cite
|
Sign up to set email alerts
|

Antecolic Versus Retrocolic Route of the Gastroenteric Anastomosis After Pancreatoduodenectomy

Abstract: The route of GE reconstruction after PD does not influence the postoperative incidence of DGE or other complications. The etiology and treatment of DGE, which occurs frequently after both procedures, need further investigation. The GE reconstruction after PD should be routed according to the surgeon's preference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
133
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(148 citation statements)
references
References 53 publications
7
133
1
7
Order By: Relevance
“…Hiyoshi et al evaluated gastric emptying and nutritional status after both procedures during a 12-month period (53). In this study, gastric emptying was evaluated by 13 C-acetate breath test before and after surgery. Interestingly, gastric emptying time in the pylorus-preserving group was better preserved than in the pylorus-resecting group when compared to the preoperative function indicating faster gastrointestinal passage after pylorus resection.…”
Section: Pylorus-preserving Versus Pylorus-resecting Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Hiyoshi et al evaluated gastric emptying and nutritional status after both procedures during a 12-month period (53). In this study, gastric emptying was evaluated by 13 C-acetate breath test before and after surgery. Interestingly, gastric emptying time in the pylorus-preserving group was better preserved than in the pylorus-resecting group when compared to the preoperative function indicating faster gastrointestinal passage after pylorus resection.…”
Section: Pylorus-preserving Versus Pylorus-resecting Pdmentioning
confidence: 99%
“…Occurring in up to 61% of patients, delayed gastric emptying (DGE) is the most frequent complication after PD (13). One major argument against pylorus preservation has been the hypothesis that the pylorus plays a pivotal role in the pathophysiology of DGE as devascularization and denervation of the pylorus may result in pylorospasm (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…table 1; for all online suppl. material, see www.karger.com/doi/10.1159/000441480) [16,[18][19][20][21][22] . These RCTs included a total of 588 patients (296 in the antecolic group and 292 in the retrocolic group).…”
Section: Included Studiesmentioning
confidence: 99%
“…Since the available evidence remains conflicting, there is an ongoing debate as to whether an antecolic or retrocolic (through the mesocolon) reconstruction should be favored. Some retrospective studies and randomized controlled trials (RCTs) have shown that the antecolic method is associated with fewer DGE [15,17,18,21,26] , but other studies found no difference [16,19,20,22,23] . Three specific meta-analyses were performed: two concluding that the antecolic reconstruction was superior [25,27] and one finding that there was no difference [28] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation